(15+2x)(9+2x)-15*9=112

Simple and best practice solution for (15+2x)(9+2x)-15*9=112 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (15+2x)(9+2x)-15*9=112 equation:



(15+2x)(9+2x)-15*9=112
We move all terms to the left:
(15+2x)(9+2x)-15*9-(112)=0
determiningTheFunctionDomain (15+2x)(9+2x)-112-15*9=0
We add all the numbers together, and all the variables
(2x+15)(2x+9)-112-15*9=0
We add all the numbers together, and all the variables
(2x+15)(2x+9)-247=0
We multiply parentheses ..
(+4x^2+18x+30x+135)-247=0
We get rid of parentheses
4x^2+18x+30x+135-247=0
We add all the numbers together, and all the variables
4x^2+48x-112=0
a = 4; b = 48; c = -112;
Δ = b2-4ac
Δ = 482-4·4·(-112)
Δ = 4096
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{4096}=64$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(48)-64}{2*4}=\frac{-112}{8} =-14 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(48)+64}{2*4}=\frac{16}{8} =2 $

See similar equations:

| 99=3r | | 3n-8n=-5 | | 6(−3x+8)=−6(8x−8) | | -7+p/9=9 | | 40=2t | | x^-5x-84=20 | | 0.15(y​-0.2)=2-​0.5(1​-y) | | F(x)=5(x-5)+17 | | 3(×-27)=12x | | v+2=20 | | 5(x+2)-3=3x-8x-7 | | 4-6(x+2)=2 | | 6+2j=2j+6 | | 5x=(4x+10) | | 6(-k-3)=24 | | 82=g-19 | | 137=-y+208 | | 2=g+(-3) | | 12x+5=20x+12 | | 38+6x=86 | | 82=g—-19 | | 3.4x=10 | | 2x+26+172=146+2x | | 20.00=0.02m | | 10/3=x/(-6/2) | | 9-6h=h-9-5h | | (5x+20)(x+80)=180 | | 51=6t+3 | | -w-2=7-w | | -2+x/6=3 | | 6+3b=1-2b+5b | | r+57=-36 |

Equations solver categories